2016
DOI: 10.1108/pr-09-2014-0203
|View full text |Cite
|
Sign up to set email alerts
|

HRM in healthcare: the role of work engagement

Abstract: Purpose: Due to increasing cost pressures, and the necessity to ensure high quality patient care while maintaining a safe environment for patients and staff, interest in the capacity for HRM practices to make a difference has piqued the attention of healthcare professionals. The purpose of this study is to present and test a model whereby engagement mediates the relationship between four HRM practices and quality of care and safety in two different occupational groups in healthcare, namely, nurses and administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 82 publications
(110 reference statements)
5
86
0
1
Order By: Relevance
“…It is suggested that employees who perceive they are managed with positive HRM practices are likely to demonstrate improved performance and competence, which is likely to positively affect organizational outcome . Our review found that CBHRM affects the quality of health care, patient safety, and patient satisfaction . Thus, if we want to drive important organizational outcomes, a good strategy to start with is focusing on “people.”…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that employees who perceive they are managed with positive HRM practices are likely to demonstrate improved performance and competence, which is likely to positively affect organizational outcome . Our review found that CBHRM affects the quality of health care, patient safety, and patient satisfaction . Thus, if we want to drive important organizational outcomes, a good strategy to start with is focusing on “people.”…”
Section: Resultsmentioning
confidence: 99%
“…A very recent systematic review (Keyko, Cummings, Yonge, & Wong, 2016) extensively explored the relationships between antecedents of work engagement and outcomes within the context of professional nursing practice and highlighted the importance of work engagement for quality of care, voice behaviour, patient satisfaction, work effectiveness, and productivity. Other reviews support these findings (e.g., Bailey, Madden, Alfes, & Fletcher, 2015;Bargagliotti, 2012), and a number of empirical studies in healthcare settings have also noted the importance of participation in decision-making, training, trust in a manager, and authentic leadership for work engagement, quality of care, and safety outcomes (Laschinger & Leiter, 2006;Saka, A. M. 2006;Shantz, Alfes, & Arevshatian, 2016;Wong, Lashinger, & Cummings, 2010). Taken together, these findings suggest that an intervention designed to increase the work engagement of healthcare workers will be particularly successful and appropriate on hospital wards where older people are cared for.…”
Section: Intervention Contextmentioning
confidence: 87%
“…In the remaining studies, researchers have benefited from other modeling approaches, such as multilevel linear regression, Bayesian methods, or canonical discriminant analysis (Table 7). Alessandri et al, 2018;Alfes and Truss, 2013;Ali et al, 2018;Anitha, 2014;Bakker et al, 2012;Barnes and Collier, 2013;Benn et al, 2015;Castanheira, 2016;Chughtai and Buckley, 2011;Coco and Jamison, 2011;Eldor, 2017;Findikli, 2015;Freeney and Fellenz, 2013;Gorgievski and Moriano, 2014;Gutermann et al, 2017;Halbesleben and Wheeler, 2008;Karatepe and Olugbade, 2016;KaĆĄpĂĄrkovĂĄ et al, 2018;Kataria et al, 2013;Kim and Koo, 2017;Kovjanic and Schuh, 2013;Lathabhavan et al, 2017;Lazauskaite-Zabielske et al, 2018;Lorente and Salanova, 2014;Maden, 2015;Medlin and Green, 2009;Medlin et al, 2016;Myrden and Kelloway, 2015;Nazir and Islam, 2017;Park et al, 2017;Reijseger et al, 2017;Salanova and Agut, 2005;Shantz and Alfes, 2013;Shantz et al, 2016;Suan Choo, 2016;Suhartanto and Brien, 2018;Tims and Bakker, 2013;Tims et al, 2015;…”
Section: Statistical Analysis: Methods Used By Authors Of Analyzed Stmentioning
confidence: 99%
“…Research using the particular scale UWES-9 [Schaufeli et al, 2002] 9 items rated on 7-point scale: 3 vigor items, 3 dedication items, and 3 absorption items 47 studies: Akhtar et al, 2016;Alessandri et al, 2018;Ali et al, 2018;Bakker and Bal, 2010;Bakker et al, 2012;Bal and De Lange, 2015;Castanheira, 2016;CesĂĄrio and Chambel, 2017;Chughtai and Buckley, 2011;Dijkhuizen et al, 2016;Eldor and Harpaz, 2016;Eldor, 2017;Findikli, 2015;Fletcher, 2016;Freeney and Fellenz, 2013;Gordon and Demerouti, 2015;Gorgievski and Moriano, 2014;Gutermann et al, 2017;Kapil and Rastogi, 2017;Karatepe, 2011;Karatepe and Olugbade, 2016;KaĆĄpĂĄrkovĂĄ et al, 2018;Kataria et al, 2013;Kovjanic and Schuh, 2013;Lathabhavan et al, 2017;Lorente and Salanova, 2014;Maden, 2015;MĂ€kikangas et al, 2016;Myrden and Kelloway, 2015;Nazir and Islam, 2017;Park et al, 2017;Rahman et al, 2017;Reijseger et al, 2017;Schmitt et al, 2016;Shantz and Alfes, 2013;Shantz et al, 2016;Shuck and Zigarmi, 2015 1 ;Steffens and Haslam, 2014;…”
Section: Scalementioning
confidence: 99%